Tracing the roots: understanding the factors that drive motivation and loyalty of scholars toward joining international academic conferences - Williady, Angellie; Handani, Narariya Dita; Wang, Jue; Kim, Hak-Seon (Frontiers in Education, 2024)
This study aims to examine the factors contributing to motivation and loyalty among scholars attending international academic conferences. Specifically, the study aims to understand what motivates scholars to participate actively in these events by investigating the interaction between academic skills, academic self-concept, support, motivation, and loyalty. Data were collected from 238 respondents to a structured questionnaire distributed at three international conferences in Indonesia, South Korea, and India. As a result of these findings, academic skills (β = 0.453, t-value = 5.128) and self-concept (β = 0.358, t-value = 3.963) significantly influence perceived support, which encourages motivation and fosters loyalty toward these conferences. Furthermore, motivation serves as a critical mediator, bringing together academic skills and self-esteem with loyalty, suggesting that nurturing these elements has a significant impact on scholars’ engagement and commitment to the academic community.